ANALISIS PUTUSAN PIDANA MATI TERHADAP PELAKU TINDAK PIDANA NARKOTIKA DAN PSIKOTROPIKA - Zainab Ompu Jainah (Law Faculty of Universitas Bandar Lampung, 2019)
ABSTRAK The imposition of capital punishment on narcotics and psychotropic criminals in Indonesia in the perspective of human rights based on the 1945 Constitution needs to be reviewed to understand whether capital punishment is a way of law enforcement that is contrary to human rights. The main problem being the object of research, is the imposition of capital punishment against narcotics and psychotropic criminals violating human rights based on the 1945 Constitution. This research is a normative legal research through a legislative approach, conceptual, case. The data used is secondary data with qualitative data analysis. The results of the study show that the imposition of capital punishment on narcotics and psychotropic criminals does not violate human rights because it does not conflict with the provisions of Article 28A, Article 28I paragraph (1) and Article 28J paragraph (2) of the 1945 Constitution and does not violate Indonesia's international legal obligations that were born from international agreements on the eradication of illicit trafficking in narcotics and psychotropic substances. As a suggestion, law enforcement needs to be improved, because crime / narcotics and psychotropic crimes are transnational types of crime by using high modus operandi.